Stretchable wiring board and method for manufacturing the stretchable wiring board
An elastic wiring board with a gold thin film and optimized microcrack morphology, formed using electroless plating on an elastic substrate with a primer layer, addresses the challenge of balancing conductivity and elasticity for wearable devices, achieving effective performance across various extension ratios.
Patent Information
- Application Number
- JP2024041989
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-07
- Filing Date
- 2024-03-18
- Publication Date
- 2025-03-19
AI Technical Summary
Existing elastic wiring boards with gold thin films struggle to achieve a balance between low initial resistance and high extension ratios, while maintaining conductivity and biocompatibility for wearable devices.
The development of an elastic wiring board with a substrate made of an elastic elastomer, a primer layer containing a crosslinking agent, and a gold thin film formed using electroless plating, which optimizes the morphology of microcracks for enhanced conductivity and elasticity.
The proposed solution achieves excellent conductivity and elasticity, with a normalized resistance ratio of 35 or less at a 50% extension rate, and a sheet resistance of 10 Ω/sq or less when non-stretched, making it suitable for wearable devices and healthcare applications.
Smart Images

Figure 2025038850000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a stretchable wiring board in which a wiring material made of a gold thin film is formed on a predetermined base material having stretchability, and in particular to a stretchable wiring board having excellent elongation and suitable electrical conductivity. [Background technology]
[0002] Research into flexible electronics that can follow flexures and undulations while retaining electrical conductivity has been ongoing for a long time. In recent years, stretchable electronics, which go beyond flexible electronics and are also endowed with elasticity, have been attracting attention. In particular, with the recent growing interest in improving people's health and the development of the IoT field, such as remote medical care, it is expected that stretchable electronics will be applied in the fields of wearable devices and healthcare devices that can acquire daily vital data consciously or unconsciously. Furthermore, it is expected that stretchable electronics will also be used to respond to artificial skin and skin sensors for robots.
[0003] When applying stretchable electronics to various devices, a stretchable wiring board is used in which a wiring material made of a conductive material is formed on a stretchable base material made of resin, rubber, etc. Such a stretchable wiring board is required to have not only electrical properties that are usually required for wiring boards, such as reduced resistance value (sheet resistance), but also biocompatibility and high stretchability in consideration of application to human skin, etc. In this regard, among the stretchable wiring boards to date, those that use conductive polymers or liquid metals that have both conductivity and stretchability as wiring materials are known. However, conductive polymers are insufficient in terms of electrical properties. In addition, liquid metals may stick to and remain on the skin when putting on and taking off, cutting off electrical continuity, and also have a poor wearing comfort.
[0004] Therefore, from the viewpoint of electrical conductivity and dimensional stability, it is preferable to use a metal in a solid state as the wiring material for the stretchable wiring board. When applying a metal to a stretchable wiring board, the challenge is how to optimize the balance between electrical conductivity and stretchability of the wiring material made of the metal.
[0005] Here, the inventor of the present application has developed a stretchable wiring substrate in which a resin (polydimethylsiloxane: PDMS) is used as a stretchable substrate, and a gold thin film is formed thereon by vacuum deposition as a wiring material (Non-Patent Document 1). The gold thin film of this stretchable wiring substrate contains a number of fine cracks (microcracks) in the formed state. Each microcrack absorbs distortion by expanding and contracting according to the expansion and contraction of the substrate, and as a result, the gold thin film can expand and contract without peeling off from the substrate. The structure of such a gold thin film having microcracks is called "kirigami-structures" due to the above-mentioned deformation mode. A gold thin film having a kirigami-structure prevents wiring breakage by cracks that expand in various places when stretched, and maintains conductivity by the crack-free areas functioning as conductive paths.
[0006] In the study of this prior art, it is said that the size and shape of the microcracks in the gold thin film during film formation and elongation can be made suitable by controlling the deposition rate of the gold thin film by vacuum deposition. This makes it possible to obtain a stretchable wiring board that has low resistance (sheet resistance: 12 Ω / sq) at the initial resistance before elongation (elongation rate 0%) and maintains conductivity even when the elongation rate is 50% or more. [Prior art documents] [Non-patent literature]
[0007] [Non-Patent Document 1] N. Matsuhisa et al. “High‐Transconductance Stretchable Transistors Achieved by Controlled Gold”. Adv. Elect.Materials,2019(5),p1900347. Summary of the Invention [Problem to be solved by the invention]
[0008] The stretchable wiring substrate with a gold thin film that exhibits the above-mentioned Kirigami-like structure due to microcracks is based on a unique idea that actively utilizes the expansion of cracks, which is usually avoided, to impart stretchability. Furthermore, since gold is a metal that has excellent electrical conductivity as well as good chemical stability and biocompatibility, it is expected to be applied to the above-mentioned wearable devices, etc.
[0009] However, there is still room for improvement in the stretchable wiring board having the gold thin film having the kirigami-like structure due to the above-mentioned microcracks. That is, as described above, the stretchable wiring board is required to have a lower initial resistance and a higher elongation rate. It is difficult to say that the stretchable wiring boards to date have fully met this requirement.
[0010] The present invention has been made under the above circumstances, and aims to provide a stretchable wiring board with improved electrical conductivity and stretchability. As a specific method, a stretchable wiring board is presented in which a gold thin film formed by a process different from that of the conventional technology is used as a wiring material. [Means for solving the problem]
[0011] In order to solve the above problems, the present inventors have decided to study the optimization of the formation method of a gold thin film while applying it as a wiring material. As a method for forming a thin metal film (film formation method), in addition to the vacuum deposition applied in the above-mentioned conventional technology, various film formation processes such as plating and chemical vapor deposition are known. Metal thin films formed by these various film formation processes have little difference in external characteristics such as purity and density. However, if the film formation process is different, the film formation mechanism will also be different, and it is considered that the bonding state of metal particles (metal atoms) will be different due to the difference. The present inventors have considered that the bonding state of the metal particles affects the shape of the microcracks introduced during film formation and the state of the microcracks during elongation.
[0012] As a result of intensive research, the present inventors have found that a gold thin film formed by electroless plating (autocatalytic electroless plating) that has undergone a specific process can have a good microcrack shape during extension. The specific process is a process in which a primer layer of a predetermined component is formed on a substrate, and then a gold thin film is formed by electroless plating. The configuration and function of the primer layer will be described in detail later, but in addition to acting as an adhesion auxiliary layer for the gold thin film, the primer layer also captures a catalyst made of gold nanoparticles used during electroless plating, contributing to the formation of a gold thin film in a favorable state.
[0013] Furthermore, the present inventors conducted detailed studies on the stretchable wiring board composed of the above-mentioned substrate, primer layer, and thin gold film. As a result, the present inventors considered that the strength of the substrate also affects the shape of microcracks in the thin gold film. Specifically, they discovered that by setting the strength of the substrate within a certain range, the shape of the cracks in the thin gold film during stretching can be made favorable, thereby ensuring good electrical conductivity, and thus arrived at the present invention.
[0014] That is, the present invention is an elastic wiring board comprising a substrate made of an elastic elastomer, a primer layer formed on at least one surface of the substrate, the primer layer comprising at least a resin component and a crosslinking agent containing an amino group, and a thin gold film formed on the primer layer, the substrate being an elastic wiring board having a Young's modulus of 7 MPa or more and 100 MPa or less.
[0015] The configuration and conductive properties of the stretchable wiring board according to the present invention will be described below, and a method for producing the stretchable wiring board will be described in detail.
[0016] A Stretchable Wiring Board According to the Present Invention The stretchable wiring board according to the present invention comprises, as essential components, a substrate, a primer layer, and a thin gold film. These components will be described in detail below.
[0017] A-1 Base material The substrate is a member for supporting the gold thin film, which is the wiring material. In the present invention, the substrate is made of an elastic elastomer. Elastomer is a general term for a polymeric material having viscoelasticity, and preferably contains at least one resin selected from the group consisting of urethane resin, silicone resin, acrylic resin, and olefin resin. In the present invention, the Young's modulus, which indicates the strength of the elastic elastomer, which is the substrate, is set to be in the range of 7 MPa to 100 MPa.
[0018] In the present invention, in which the gold thin film is given extensibility by expanding the microcracks and controlling their morphology, there are several factors that affect the behavior of the microcracks. The mechanical properties of the substrate, particularly the Young's modulus, are one of the most important factors. When the difference in mechanical properties between the substrate and the gold thin film is large, a local stress concentration portion is formed in the gold thin film, and the crack expansion proceeds excessively. In detail, a substrate with a Young's modulus of less than 7 MPa has a large strength difference with the gold thin film and the primer layer, and the strain cannot be uniformly transmitted to the entire gold thin film during extension, so some cracks expand excessively and the sheet resistance increases. On the other hand, the upper limit of the strength of the substrate is set to 100 MPa, because a substrate with excessively high strength has difficulty in following the extension due to the movement of the living body. The Young's modulus of the substrate is more preferably 8 MPa or more and 50 MPa or less.
[0019] Considering the above-mentioned preferable conditions, specific examples of the elastic elastomer to be used as the base material include thermoplastic elastomers of urethane type (TPU), ester type (TPEE), amide type (PEBA), and olefin type (TPV). Among these elastomers, those having the above-mentioned Young's modulus are suitable for the base material.
[0020] A-2 Primer layer In the present invention, the primer layer is a functional layer having multiple functions, and is an essential component of the present invention. That is, the primer layer acts as an adhesion auxiliary layer to ensure adhesion between the gold thin film and the substrate. It also has the function of reducing the strength difference between the gold thin film and the substrate, and optimizing the state of microcracks that expand during elongation. As described above, in the present invention, the strength (Young's modulus) of the substrate is specified. The primer layer further reduces the strength difference between the gold thin film and the substrate, and acts on the form of microcracks during elongation.
[0021] An important further function of the primer layer is the capture of nano catalyst particles when forming a gold thin film by electroless plating. The formation of a gold thin film by electroless plating itself is possible without nano catalyst particles due to the action of a reducing agent in the plating solution. However, in the electroless plating method, by fixing an appropriate nanoparticle catalyst on the substrate, it is possible to improve the adhesion of the gold thin film and optimize the film formation speed and thin film quality. The action of such nanoparticle catalysts is also useful for controlling the shape of microcracks in the gold thin film. Furthermore, by selectively fixing the nanoparticle catalyst on the substrate, it is possible to form fine gold thin film wiring. Therefore, in the stretchable wiring board according to the present invention, a primer layer having a nanocatalyst capture action is an essential component.
[0022] The primer layer essentially contains a resin component and a crosslinking agent. The resin is a component for maintaining the solid form of the primer layer, and the crosslinking agent is a component for forming the primer layer by crosslinking the molecules of the resin component through a crosslinking reaction to insolubilize the resin. In the present invention, the crosslinking agent is a compound that generates a specific functional group (amino group) during the crosslinking reaction. This functional group is generated to capture a nanoparticle catalyst in the electroless plating process after the formation of the primer layer. The nanoparticle catalyst captured by the functional group contributes to the formation of a thin gold film in the electroless plating process.
[0023] The resin component of the primer layer can be selected from epoxy resins, phenolic resins, cyanate resins, isocyanate resins, benzoxazine resins, oxetane resins, polyester resins, allyl resins, dicyclopentadiene resins, etc. As the resin component, those containing at least one of epoxy resins and polyester resins are particularly preferred.
[0024] On the other hand, as described above, the crosslinking agent is a compound that crosslinks resin molecules by a crosslinking reaction to generate functional groups (amino groups). Specifically, melamine-based crosslinking agents, amine-based crosslinking agents, guanamine-based crosslinking agents, glycoluril-based crosslinking agents, etc. can be used. A particularly suitable crosslinking agent is a melamine-based crosslinking agent. Melamine-based crosslinking agents include methoxyalkyl melamines such as hexamethoxymethylmelamine / hexamethoxyethylmelamine (HMM), dimethoxymethylmelamine, trimethoxymethylmelamine, tetramethoxymethylmelamine, pentamethoxymethylmelamine, and hexamethoxymethylmelamine. In addition, there are alkoxymethylglycolurils such as tetramethoxymethylglycoluril, 1,3-bismethoxymethyl-4,5-bismethoxyethyleneurea, and bismethoxymethylurea.
[0025] The primer layer contains at least a resin component and a crosslinking agent, but may contain components other than these essential components. As described later, the primer layer is formed by applying a primer liquid in which a resin component and a crosslinking agent are dispersed or dissolved in a solvent to a substrate and baking it. Such primer liquids often contain auxiliary components such as a photoacid generator and a sensitizer. When a primer layer is formed from a primer liquid, it may contain substances derived from these auxiliary components, and such components may be included.
[0026] In the stretchable wiring board according to the present invention, the thickness of the primer layer described above is preferably 400 nm or more and 1000 nm or less. If the primer layer is too thick or too thin, the resistance value during elongation tends to be high. This is presumably due to the conductive path becoming longer due to the form of cracks during elongation. The thickness of the primer layer is more preferably 450 nm or more and 800 nm or less.
[0027] A-3 Gold thin film (gold wiring) The wiring material of the stretchable wiring board according to the present invention is made of gold. As described above, gold is a wiring material with excellent electrical conductivity. In addition, gold has high chemical stability and biocompatibility, making it suitable as a wiring material for wearable devices and healthcare devices.
[0028] In the stretchable wiring board according to the present invention, the gold thin film, which is the wiring material, is preferably 60 nm or more in thickness. Usually, the resistance value of the wiring board decreases in inverse proportion to the increase in the thickness of the wiring material. In the present invention, by making the gold thin film 60 nm or more in thickness, it is possible to exhibit a resistance value suitable for the wiring material. In addition, a gold thin film having a thickness of 60 nm or more can be formed by vacuum deposition, which is a conventional technology. However, when the thickness of a gold thin film formed by vacuum deposition increases, the resistance value during extension tends to become excessive. In the present invention, by restricting the mechanical properties of the base material and applying a primer layer as described above, the stretchable wiring board is obtained in which the resistance value during extension is less affected even if the thickness of the gold thin film is increased. The thickness of the gold thin film is more preferably 100 nm or more. In addition, the upper limit of the thickness of the gold thin film is preferably 1000 nm or less. If the thickness is too large, there is a risk of breakage during extension.
[0029] It is more preferable that the gold thin film in the present invention has a suitable unevenness (roughness) on the surface. By having a certain degree of roughness, the gold thin film can have good elasticity from a structural standpoint. Specifically, the roughness of the gold thin film is preferably such that the arithmetic mean roughness (Sa) of the gold thin film surface is 0.2 μm or more and the maximum height (Sz) is 3.5 μm or more. It is more preferable that Sa is 0.5 μm or more.
[0030] B. Conductive properties of the stretchable wiring board according to the present invention when stretched As described above, the stretchable wiring board according to the present invention can be stretched by the expansion of microcracks contained in the gold thin film, which is the wiring material, and the shape of the cracks during stretching ensures conductivity. In the present invention, multiple microcracks in the gold thin film during stretching are formed on the surface of the gold thin film, and have a length (crack length) in a direction intersecting the stretching direction. The microcracks increase in length and width as the stretching rate increases. However, the microcracks do not completely traverse the gold thin film, and a continuous gold layer serving as a conductive path is formed.
[0031] The expanded microcracks observed on the gold thin film surface form various shapes such as a mesh-like or spider-web-like shape as the elongation rate increases. In the present invention, the shape of the microcracks itself has little effect on maintaining the conductivity of the gold thin film. The conductivity of the gold thin film during elongation is greatly affected by whether the microcracks expand uniformly in the plane. If the distribution of the microcracks is non-uniform and the microcracks are locally dense, it becomes difficult for the relevant area to function as a conductive path. Therefore, the preferred shape of the microcracks during elongation of the stretchable wiring board according to the present invention can be qualitatively explained as above. However, it is difficult to specify quantitative and numerical elements for the shape of the cracks during elongation.
[0032] The normalized resistance at a predetermined elongation rate is useful for identifying the form of microcracks when the gold thin film is stretched. The normalized resistance is expressed as the ratio (R / R0) of the resistance R (Ω) at the time of elongation when stretched at a predetermined elongation rate to the initial resistance R0 (Ω) before elongation (elongation rate 0%). When the film thickness of the thin film is small, the resistance of the wiring does not change much even if the elongation rate increases. When the film thickness is large, the resistance of the wiring tends to change under the influence of the elongation rate. In the present invention, it is assumed that a gold thin film with a relatively large film thickness is applied in consideration of reducing the initial resistance. In the stretchable wiring board of the present invention, the rate of change in resistance is relatively small even in a thick gold thin film. This is considered to be based on the form of microcracks.
[0033] Specifically, the stretchable wiring board according to the present invention can have a ratio R / R0 of the resistance R at elongation when elongated at an elongation rate of 50% to the initial resistance R0 of 35 or less. It is believed that the relatively small value of such normalized resistance is due to the form of cracks in the gold thin film at the time of elongation. It is more preferable that R / R0 at elongation at an elongation rate of 50% is 25 or less. Note that the reason why the normalized resistance at an elongation rate of 50% is referred to in the present invention is because when the stretchable wiring board is used on the skin of the human body, 50% is assumed to be the required elongation rate. Also, by definition, the value of the normalized resistance R / R0 is 1 or more.
[0034] The elastic wiring board according to the present invention can achieve low resistance when not stretched (0% stretch rate) by optimizing the thickness of the gold thin film, etc. The elastic wiring board according to the present invention can have a sheet resistance of 10 Ω / sq or less when not stretched. The sheet resistance when not stretched is more preferably 5 Ω / sq or less.
[0035] C. Manufacturing method of the stretchable wiring board according to the present invention Next, a method for producing a stretchable wiring board according to the present invention will be described. The stretchable wiring board according to the present invention can be produced by sequentially forming a primer layer and a gold thin film on a substrate. In the present invention, electroless plating is applied as a process for forming the gold thin film. That is, the method for producing a stretchable wiring board according to the present invention is a method for producing a stretchable wiring board comprising a substrate made of a stretchable elastomer, a primer layer formed on at least one surface of the substrate, and a gold thin film formed on the primer layer, and includes a step of forming the primer layer by applying a primer liquid containing at least a resin and a crosslinking agent containing an amino group to the substrate, a step of dispersing a gold nanoparticle catalyst having a particle size of 1 nm to 100 nm and made of gold on the surface of the primer layer, and a step of forming a gold thin film on the surface of the primer layer by an electroless plating method. Each step of the stretchable wiring board according to the present invention will be described below.
[0036] C-1 Base material preparation The substrate is made of an elastic elastomer having the above-mentioned predetermined Young's modulus. The substrate may be processed before the primer layer is formed. If necessary, the substrate may be subjected to a pretreatment such as a cleaning treatment.
[0037] C-2 Formation of primer layer The primer layer is formed by applying a primer liquid containing at least a resin component and a crosslinking agent to a substrate and then promoting a crosslinking reaction of the resin molecules. In addition, in order to form a desired wiring pattern, a deactivation treatment may be performed on the functional groups activated by the crosslinking reaction.
[0038] The primer liquid is a solution containing a resin and a crosslinking agent as essential components, which are dissolved in a solvent.
[0039] The resin can be selected from the above-mentioned specific examples, such as epoxy resin, phenol resin, cyanate resin, isocyanate resin, benzoxazine resin, oxetane resin, polyester resin, allyl resin, dicyclopentadiene resin, etc. Resins such as epoxy resin and polyester resin are preferably used.
[0040] The crosslinking agent is a component for crosslinking the resin molecules and between the molecules to make them insoluble after the primer liquid is applied. In the present invention, the crosslinking agent also has the effect of generating functional groups (amino groups) during the crosslinking reaction. The functional groups thus generated capture the gold nanoparticle catalyst described below, accelerating the formation of a thin gold film by plating.
[0041] The crosslinking agent is not particularly limited as long as it has the above-mentioned crosslinking reaction and functional group generation action, but melamine-based crosslinking agents, amine-based crosslinking agents, guanamine-based crosslinking agents, glycoluril-based crosslinking agents, etc. can be used. A particularly suitable crosslinking agent is a melamine-based crosslinking agent. Melamine-based crosslinking agents include methoxyalkyl melamines such as hexamethoxymethylmelamine / hexamethoxyethylmelamine (HMM), dimethoxymethylmelamine, trimethoxymethylmelamine, tetramethoxymethylmelamine, pentamethoxymethylmelamine, hexamethoxymethylmelamine, etc. In addition, there are alkoxymethylglycolurils such as tetramethoxymethylglycoluril, 1,3-bismethoxymethyl-4,5-bismethoxyethyleneurea, bismethoxymethylurea, etc.
[0042] In addition to the essential components of resin and crosslinking agent, the primer liquid may contain auxiliary components such as photoacid generators and sensitizers as reaction initiators. Examples of photoacid generators include onium salts (sulfonium salts, iodonium salts, diazonium salts, etc.), nitrobenzyl esters, diazomethane, triazines, etc., used alone or in combination. Examples of sensitizers include 9-methylanthracene, anthracenemethanol, acenaphthylene, thioxanthone, methyl-2-naphthyl ketone, 4-acetylbiphenyl, 1,2-benzofluorene, etc.
[0043] The primer liquid is composed of the resin, the crosslinking agent, and the auxiliary components dissolved in a solvent. Ketones, ethers, esters, aromatic hydrocarbons, and the like can be used as the solvent for the primer liquid. Specific examples of the solvent include methyl ethyl ketone, methyl isobutyl ketone, 2-heptanone, cyclopentanone, cyclohexanone, 2-methoxy-1-propylene acetate, 2-methoxyethanol, 2-ethoxyethanol, 2-ethoxyethyl acetate, 1-methoxy-2-propyl acetate, 1,2-dimethoxyethaneethyl acetate, cellosolve acetate, propylene glycol monoethyl ether acetate, propylene glycol methyl ether acetate, methyl lactate, ethyl lactate, methyl pyruvate, ethyl pyruvate, ethyl 3-methoxypropionate, N-methyl-2-pyrrolidone, 1,4-dioxane, ethylene glycol monoisopropyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether, diethylene glycol dimethyl ether, and toluene.
[0044] Regarding the concentration and compounding ratio of the resin and crosslinking agent in the primer liquid, the compounding ratio of the essential components, resin and crosslinking agent, in the primer liquid is preferably 1:1 to 1.5:1 by mass. When the resin and crosslinking agent are diluted with a solvent to prepare the primer liquid, the amount of the solvent used is preferably 20% by mass or more and 75% by mass or less with respect to the entire primer liquid.
[0045] The primer liquid can be applied to the substrate by various methods, including spraying, dipping, spin coating, roll coating, and various printing methods (screen printing, gravure printing, flexographic printing, inkjet printing, etc.). After application of the primer liquid, it is preferable to perform a drying process, which can be performed at room temperature or under heating conditions. The thickness of the primer layer after drying can be adjusted by the concentrations of the resin and crosslinking agent in the primer liquid and the application conditions of the primer liquid.
[0046] After the primer liquid is applied, the crosslinking reaction of the resin is advanced by the crosslinking agent to form a primer layer. The crosslinking reaction is initiated and advanced by heating or light irradiation. The heat treatment is preferably performed at 100°C or higher. The light irradiation is preferably performed using a light source with a wavelength of 300 nm or more. As the crosslinking reaction advances, the crosslinking of the resin advances to form a primer layer, and at the same time, the functional group (amino group) of the crosslinking agent component is activated.
[0047] In addition, the functional group (amino group) generated by the above-mentioned crosslinking reaction is in an active state, but this functional group is inactivated by irradiation with deep ultraviolet light having a wavelength of less than 300 nm. Such inactivation of the functional group contributes to the selective fixation of the gold nanoparticle catalyst, which will be described later. By patterning with a photomask or the like and irradiating with deep ultraviolet light, a wiring pattern of the gold thin film can be formed.
[0048] C-3 Gold nanoparticle catalyst In the present invention, a gold thin film is formed on the primer layer formed as described above by electroless plating, and a nanoparticle catalyst made of gold is fixed to the surface of the primer layer as a pretreatment. The gold nanoparticle catalyst is bound to and fixed with the functional group that has become active during the formation process of the primer layer described above, and promotes the deposition of gold in the subsequent electroless plating process. The gold nanoparticle catalyst can improve the adhesion between the gold thin film and the primer layer. The application of the gold nanoparticle catalyst is essential in order to form a gold thin film that is affected by the expansion and contraction of the substrate.
[0049] The gold nanoparticle catalyst is a fine particle made of gold, and its average particle size is preferably 2 nm to 100 nm. The gold nanoparticle catalyst is preferably in a monodispersed state, and if the particle size is too small, it tends to aggregate, so it is set to 2 nm or more. In addition, gold nanoparticle catalysts with excessively large particle sizes have a reduced ability to bind to functional groups in the primer layer. The average particle size of the gold nanoparticle catalyst is preferably 5 nm to 50 nm.
[0050] When fixing the gold nanoparticle catalyst to the primer layer, it is preferable to apply a dispersion of the gold nanoparticle catalyst to the surface of the primer layer. In this case, the dispersion medium of the dispersion of the gold nanoparticle catalyst is preferably an aqueous solution containing a sugar alcohol. The sugar alcohol binds to the gold nanoparticle catalyst and acts as a protective agent (dispersant) to suppress the aggregation of the gold nanoparticle catalyst in the dispersion. In addition, the sugar alcohol bound to the gold nanoparticle catalyst in the dispersion is substituted for the functional group on the surface of the primer layer, promoting the binding between the gold nanoparticle catalyst and the (functional group of) the primer layer. As the sugar alcohol as such a protective agent, glycerin, erythritol, xylitol, sorbitol, mannitol, etc. can be applied. And, the dispersion medium is preferably an aqueous solution containing 0.1 g / L or more and 20 g / L or less of a sugar alcohol.
[0051] Here, the number (density) of gold nanoparticle catalysts fixed on the primer layer may affect the properties of the thin gold film formed in the subsequent electroless plating process.
[0052] Specifically, in the process of dispersing the gold nanoparticle catalyst on the surface of the primer layer, the gold nanoparticle catalyst is dispersed at a density of 300 particles / μm 2 More than 1500 pieces / μm 2 It is preferable to disperse the gold nanoparticle catalyst at a density of 0.01 g / L or more and 1.0 g / L or less. The density of the gold nanoparticle catalyst can be adjusted according to the gold concentration of the gold nanoparticle catalyst dispersion and the contact time of the gold nanoparticle catalyst dispersion with the primer layer. In order to disperse and fix the gold nanoparticle catalyst at the above-mentioned suitable density, it is preferable to set the gold concentration of the gold nanoparticle catalyst dispersion to 0.01 g / L or more and 1.0 g / L or less, and to set the contact time with the primer layer to 5 minutes or more and 40 minutes or less.
[0053] The gold nanoparticle catalyst dispersion can be applied by spraying, dipping, using a spin coater, a roll coater, etc. After application of the dispersion, drying and washing may be performed as necessary.
[0054] C-4 Gold thin film deposition process (electroless plating process) In the present invention, electroless plating is applied to the process of forming a thin gold film, which is a wiring material. In particular, a process using electroless plating using an autocatalytic electroless plating solution is preferred. The autocatalytic electroless plating solution contains a gold salt, a reducing agent for reducing and depositing gold ions, and appropriate additives. A non-cyanide electroless plating solution is preferred. As the gold salt in the autocatalytic plating solution, tetrachloroauric acid (III), chloroauric acid (III), gold chloride (I), gold trifluoride (III), gold monofluoride (I), gold monobromide (I), gold tribromide (III), hydroxygold (III) oxide, triiodide gold (III), gold trisnitrate (III), gold nitrate (I), and hydrates or salts thereof are preferably used. As the reducing agent, formaldehyde, hydrazine, aminoborane, hypophosphite, etc. are preferably used.
[0055] The composition of the plating solution in the electroless plating step is preferably such that the gold concentration is maintained within the range of 1.8 g / L to 2.2 g / L. The temperature of the plating solution is preferably maintained within the range of 60° C. to 70° C. In autocatalytic electroless plating, as gold deposition begins, gold ions are continuously reduced to form a thin gold film, and the gold concentration in the plating solution decreases. For this reason, when forming a film for a long period of time, it is preferable to replenish gold salts and reducing agents so that the gold concentration is within the above range.
[0056] The thickness of the thin gold film increases with increasing plating time. In the present invention, it is preferable that the thickness of the thin gold film is 60 nm or more, and in order to achieve this thickness, the plating time is preferably 2 minutes or more.
[0057] By the above-mentioned electroless plating process, a wiring material made of a gold thin film is formed, and the stretchable wiring board according to the present invention can be obtained. Effect of the Invention
[0058] As described above, the present invention relates to an elastic wiring board having a wiring material made of a primer layer of a predetermined composition and a thin gold film formed on a substrate. The elastic wiring board according to the present invention has excellent elasticity and good conductivity when stretched. Since the present invention uses gold as the wiring material, it is also biocompatible and is expected to be applied to the fields of wearable devices and healthcare devices. [Brief description of the drawings]
[0059] [Figure 1] 4 is a graph showing the measurement results of the resistance value during stretching of the stretchable wiring board (base material: TPU, SEBS) produced in the first embodiment. [Diagram 2] 1 is a microscopic photograph of a gold thin film surface of a stretchable wiring board (base material: TPU, SEBS) manufactured in the first embodiment when stretched. [Diagram 3] 13 is a graph showing the measurement results of the resistance value during stretching of the stretchable wiring substrate (gold film thickness: 80 nm, 110 nm, 230 nm, 470 nm) manufactured in the second embodiment. [Figure 4] 6A to 6C are microscopic photographs of the gold thin film surface of the stretchable wiring substrate (gold film thickness: 80 nm, 110 nm, 230 nm, 470 nm) produced in the second embodiment when stretched. [Diagram 5] 13 is an SEM photograph of the gold thin film surface of the stretchable wiring substrate (gold film thickness: 110 nm, 230 nm, 470 nm) manufactured in the second embodiment during stretching. [Figure 6] 13 is a graph showing the measurement results of the resistance value during stretching of the stretchable wiring board (primer layer thickness: 320 nm, 450 nm, 730 nm, 1220 nm) manufactured in the third embodiment. [Figure 7] 13A and 13B are microscopic photographs of the gold thin film surface during stretching of the stretchable wiring board (primer layer thickness: 320 nm, 450 nm, 730 nm, 1220 nm) manufactured in the third embodiment. [Figure 8] 13 SEM photographs of the surface of the primer layer when the immersion time in the gold nanoparticle dispersion is changed in the fourth embodiment. [Figure 9]13 is a graph showing the results of measuring the resistance value during stretching of the stretchable wiring board (immersion time: 5 min, 20 min, 40 min) produced in the fourth embodiment. [Figure 10] 13A to 13C are microscopic photographs of the gold thin film surface during stretching of the stretchable wiring board (immersion time: 5 min, 20 min, 40 min) produced in the fourth embodiment. [Figure 11] 13 is a graph showing the results of measuring the resistance value during stretching of the stretchable wiring board (wiring width: 100 μm, 200 μm, 500 μm) manufactured in the fifth embodiment. [Figure 12] 13 is a microscopic photograph of the gold thin film surface of the stretchable wiring board (wiring width: 100 μm, 200 μm) manufactured in the fifth embodiment when stretched. [Figure 13] 13 is a graph showing the measurement results of the resistance value when the stretchable wiring board (vacuum deposition, electroless plating) manufactured in the sixth embodiment is stretched. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0060] First embodiment Hereinafter, an embodiment of the present invention will be described. In this embodiment, a primer layer and a thin gold film were formed on various resin stretchable substrates with different Young's moduli to manufacture stretchable wiring boards. Then, the initial and elongated resistance values of each stretchable wiring board were measured, and the crack morphology of the thin gold film during elongation was observed.
[0061] In this embodiment, two types of elastic elastomers, Elastollan (registered trademark) 1198ATR (manufactured by BASF Japan Ltd.: Example 1) and Miractoran (registered trademark) P22MBRNAT (manufactured by Nippon Miractoran Co., Ltd.: Example 2), which are commercially available thermoplastic polyurethane elastomers (TPU), were used as substrates. In addition, as comparative examples, H1062 and H1221 (manufactured by Asahi Kasei Chemicals Corp.: Comparative Examples 1 and 2), which are commercially available hydrogenated styrene-based thermoplastic elastomers (SEBS), from the Tuftec (registered trademark) series, were used. The measurement results of the Young's modulus of the elastic elastomers used as substrates in this embodiment are as follows.
[0062] [Table 1]
[0063] [Preparation of substrate] A 10% aqueous solution of concentrated liquid detergent (Micro90) was applied by spin coating onto a glass substrate (2000 rpm, 30 sec). The glass substrate was then annealed on a hot plate at 100°C for 1 min to form a peeling auxiliary layer. The above-mentioned elastomer solution (solvent: dimethylacetamide (DMAC), concentration: 20%) was then applied by spin coating onto the glass substrate (500 rpm, 30 sec). This was annealed on a hot plate at 110°C for 30 min to harden it. Furthermore, the surface was hydrophilized by irradiating oxygen plasma using a plasma cleaner (50 W, 5 sccm, 30 sec). By the above operations, various elastic elastomer substrates (5 cm x 7.5 cm) were produced.
[0064] [Formation of primer layer] A primer liquid was applied to the elastic elastomer substrate prepared above. The primer liquid used was the Seedcat PRM series (manufactured by EEJA Co., Ltd.), which is commercially available as a pretreatment agent for electroless plating. This pretreatment agent is composed of a resin component (Seedcat PRM A), a crosslinking agent component (Seedcat PRM B), and a reaction initiator (Seedcat PRM Starter). In this embodiment, cyclohexanone was used as a solvent, and the resin component:crosslinking agent component:reaction initiator:solvent were mixed in a mass ratio of 4:3:1:2 to prepare the primer liquid.
[0065] The primer solution was applied to the substrate by dropping 1 mL of the primer solution onto the substrate while rotating at 500 rpm for 5 seconds, and spin-coating at 1000 rpm for 30 seconds after dropping.Then, the substrate was heated on a hot plate at 110°C for 10 minutes to insolubilize the resin component and form a primer layer.
[0066] [Immobilization of gold nanoparticle catalyst] Prior to the electroless plating process, a gold nanoparticle catalyst was dispersed and fixed on the surface of the primer layer. A commercially available gold nanoparticle dispersion (Seedcat CAT-Au10: manufactured by EEJA Co., Ltd.) was used as the gold nanoparticle catalyst. The particle size of the gold nanoparticles in the dispersion was 10-30 nm, and the gold concentration was 0.1 g / L.
[0067] To fix the gold nanoparticle catalyst, the substrate on which the primer layer was formed was immersed in the gold nanoparticle dispersion liquid. In this embodiment, the immersion time was set to 20 minutes, and after the time had elapsed, the substrate was taken out and dried at room temperature.
[0068] [Gold thin film deposition] A thin gold film was formed on the substrate on which the primer layer and gold nanoparticle catalyst were fixed using an autocatalytic electroless plating solution. A commercially available non-cyan neutral autocatalytic electroless plating solution (AC FAB Au-ACG3000WX: manufactured by EEJA Co., Ltd.) was used as the electroless gold plating solution. The electroless plating process was performed by immersing the substrate in the plating solution held at 70°C for 10 minutes. After the electroless plating process, the substrate was annealed on a hot plate at 110°C for 10 minutes. The stretchable wiring board according to this embodiment was manufactured by the above process.
[0069] In addition, the gold thin film thickness of the stretchable wiring board manufactured in this embodiment was measured before various measurement tests. The film thickness was measured by cutting a part of the stretchable wiring board manufactured on the glass substrate with a scalpel to form a step, and measuring the step with a stylus profiling system (DektakXT: manufactured by Bruker Nano). In the stretchable wiring board manufactured in this embodiment, the gold thin film had a thickness of 200 nm.
[0070] [Conductivity test during extension] The stretchable wiring boards of the examples and comparative examples manufactured by the above process were subjected to a conductivity test during stretching to measure the resistance value during stretching. For this test, the stretchable wiring board formed on the glass substrate was cut into a size of 5 mm wide x 20 mm long. The cut stretchable wiring boards of the examples and comparative examples were arranged and fixed at intervals of 10 mm on a movable stage using double-sided tape and masking tape. Then, wires were attached to both ends of the wiring (gold thin film) of each stretchable wiring board using liquid metal, and connected to an LCR meter (ZM2376, manufactured by NF Corporation).
[0071] After each elastic wiring board was set on a movable stage, the movable stage was controlled by a 3-axis controller with built-in driver (CP-700D, manufactured by COMS Co., Ltd.) and the resistance value was measured for each 0.5% elongation rate from the initial state (elongation rate 0%). At this time, the resistance value was measured in an area of 5 mm wide × 10 mm long of the elastic wiring board.
[0072] [Morphological observation of gold thin film] For the stretchable wiring boards of each Example and Comparative Example, the morphology of the gold thin film surface during stretching was observed to examine the morphology of cracks. As in the above-mentioned stretched conductivity test, the stretchable wiring board was cut out from the glass substrate and fixed on a vice. Then, while stretching with the vice, the surface of the gold thin film was observed with an optical microscope.
[0073] SEM observation was also performed to observe the cracks microscopically. For SEM observation, a sample was prepared by applying a drop of instant adhesive to the surface of the stretchable wiring board stretched at a specified elongation rate, and the stretched state was fixed. This sample was attached to a Si wafer with carbon tape and observed with a SEM (Inspect F50, FEI Company).
[0074] [Results of electrical conductivity test under extension] FIG. 1 shows the measurement results of the resistance value during stretching of the stretchable wiring board manufactured in this embodiment. In this embodiment, stretchable wiring boards were manufactured using a TPU base material with a high Young's modulus (Examples 1 and 2) and an SEBS base material with a low Young's modulus (Comparative Examples 1 and 2) as the base material. As can be seen from FIG. 1, the stretchable wiring boards using the SEBS base material with a low Young's modulus in Comparative Examples 1 and 2 have high resistance values from the initial stage (when not stretched). The same is true at the stretch rate of 50%. From these results, it was confirmed that in order to reduce the resistance of the stretchable wiring board in the initial stage and during stretching, it is necessary to increase the strength of the base material.
[0075] [Observation of crack morphology during elongation] FIG. 2 shows a microscopic photograph of the gold thin film surface when the stretchable wiring board manufactured in this embodiment is stretched (stretch rate: 0%, 50%, 100%). When examining the morphology of the cracks, the gold thin film of Example 1 has a mesh-like, homogeneous crack. In addition, in Example 2, unlike Example 1, discontinuous cracks having a slightly wide arrowhead or wedge shape are formed, and the cracked areas and the crack-free base areas are in a relatively even state of intersecting, and it is considered that the base areas act as conductive paths and have good conductivity even when stretched. On the other hand, in the gold thin films of Comparative Examples 1 and 2, multiple linear cracks are formed in parallel across the observation area. In the gold thin films in which such cracks are formed, the thin film is connected at the bottom of the cracks (near the substrate), which is considered to maintain conductivity. However, since the ease of electron flow as a conductive path is not good, it is considered that the resistance is high.
[0076] Second embodimentIn this embodiment, a stretchable wiring board was manufactured while changing the thickness of the gold thin film, and its characteristics were evaluated. The same primer liquid and gold nanoparticle dispersion liquid as in the first embodiment were used on the same TPU base material as in Example 2 to form a primer layer and fix the gold nanoparticle catalyst. The primer liquid application conditions were 2000 prm and 1 min, and the other conditions were the same as in the first embodiment. Then, the same electroless plating solution as in the first embodiment was used to adjust the plating time (immersion time) to manufacture stretchable wiring boards with different gold thin film thicknesses. Then, the thickness of the gold thin film was measured after the electroless plating process. In this embodiment, the plating time was 3 min, 5 min, 10 min, and 20 min. The thicknesses of the gold thin films formed under these conditions were 80 nm, 110 nm, 230 nm, and 470 nm.
[0077] Thereafter, a conductivity test under extension and observation of the surface morphology of the gold thin film under extension were carried out in the same manner as in the first embodiment.
[0078] The resistance value and normalized resistance (R / R0) obtained as a result of the conductivity test when the stretchable wiring board manufactured in this embodiment is stretched are shown in Fig. 3. The resistance value when unstretched (stretch rate 0%) decreases as the thickness of the gold thin film increases. Considering the wiring dimensions (5 mm (W) × 10 mm (L)) in this test, the sheet resistance of the 80 nm-thick stretchable wiring board when unstretched was about 20 Ω / sq, and the sheet resistance of the 110 nm-thick stretchable wiring board when unstretched was 2.0 Ω / sq or less. And, when looking at the normalized resistance (R / R0) at an elongation rate of 50%, the stretchable wiring board with a thickness of 80 nm, which has a high initial resistance, has the lowest value, and the R / R0 value tends to increase with increasing thickness. The normalized resistance (R / R0) at an elongation rate of 50% was 25 or less in all cases. All of these can be considered to have the potential to be used as a stretchable wiring board. In particular, the stretchable wiring board with a thickness of 100 nm or more can be said to have extremely good resistance characteristics in the initial state and when stretched. Figures 4 and 5 are microscopic observation photographs and SEM photographs of the gold thin film surface when each stretchable wiring board is stretched (elongation rate: 0%, 50%, 150%). The crack morphology during stretching tends to become wider as the film thickness increases, but the cracks were relatively uniformly distributed at all film thicknesses.
[0079] Third embodiment In this embodiment, the thickness of the primer layer formed on the substrate was changed to produce an elastic wiring board. The same primer liquid as in the first embodiment was spin-coated on the same substrate as in Example 1 to form a primer layer. At this time, the primer liquid was applied at four spin-coat rates of 500 rpm, 1000 rpm, 2000 rpm, and 4000 rpm to form a primer layer. The thicknesses of the primer layers were 1220 nm (500 rpm), 730 nm (1000 rpm), 450 nm (2000 rpm), and 320 nm (4000 rpm). Then, each substrate on which the primer layer was formed was immersed in a gold nanoparticle dispersion for 20 minutes to form a gold thin film in an electroless plating process. The thickness of the gold thin film was 100 nm. Then, a conductivity test during extension and observation of the surface morphology of the gold thin film during extension were performed in the same manner as in the first embodiment.
[0080] FIG. 6 shows the results of a conductivity test during stretching of the stretchable wiring board of this embodiment. From FIG. 6, it can be seen that when the primer layer is at its thickest (1220 nm) and its thinnest (320 nm), the initial resistance value and the resistance during stretching tend to be high. It can be said that primer layers with thicknesses between these (450 nm, 730 nm) show approximately the same resistance characteristics. In addition, FIG. 7 shows microscopic observation images of the gold thin film surface of each stretchable wiring board during stretching.
[0081] Fourth embodiment In this embodiment, a thin gold film was formed by changing the number density of the gold nanoparticle catalyst fixed to the primer layer surface before the electroless plating process, and a stretchable wiring board was manufactured. A primer layer was formed on the substrate by the same process as in the first embodiment. Then, the substrate on which the primer layer was formed was immersed in a gold nanoparticle dispersion liquid for immersion times of 5 minutes, 20 minutes, and 40 minutes to fix the gold nanoparticle catalyst.
[0082] Figure 8 shows SEM images of the surface of the substrate (primer layer) after treatment with each immersion time. It can be seen that the density of the gold nanoparticle catalyst increases with increasing immersion time. The adhesion density of the gold nanoparticle catalyst was measured and calculated, and was found to be 324 particles / μm 2 (immersion time 5 min), 688 pieces / μm 2 (immersion time 20min), 1400 pieces / μm 2 (Immersion time: 40 min.)
[0083] After the above measurements, a gold thin film was formed on each substrate by electroless plating. The gold thin film had a thickness of 100 nm (plating time: about 5 min) and 200 nm (plating time: about 10 min), and two types of stretchable wiring boards were manufactured for each gold nanoparticle catalyst density. Then, a conductivity test during stretching and observation of the surface morphology of the gold thin film during stretching were performed in the same manner as in the first embodiment.
[0084] FIG. 9 shows the results of the conductivity test during stretching in the stretchable wiring board of this embodiment. FIG. 10 is a microscopic photograph of the gold thin film surface during stretching. In the stretchable wiring board with a gold thin film thickness of 100 nm, although there is some difference in the resistance value, there is no large difference due to the adhesion density of the gold nanoparticle catalyst in terms of normalized resistance. In addition, the morphology of the cracks during stretching also has little difference due to the adhesion density of the gold nanoparticle catalyst. On the other hand, in the stretchable wiring board with a gold thin film thickness of 200 nm, the normalized resistance decreases when the adhesion density of the gold nanoparticle catalyst increases to the maximum (40 min). Referring to FIG. 10, in the gold thin film with a thickness of 200 nm, the shape of the cracks changes due to the increase in the density of the gold nanoparticles, and the width of the cracks becomes shorter and narrower as the density of the gold nanoparticles increases. From the results of this embodiment, it can be said that the density of the gold nanoparticle catalyst may affect the conductivity of the stretchable wiring board depending on the thickness of the gold thin film, so it is preferable to treat it according to the film thickness.
[0085] Fifth embodiment Considering the characteristics of the primer layer (primer liquid) used in this embodiment, the formation of fine wiring using photopatterning was investigated. The crosslinking agent component of the primer liquid used in this embodiment activates the functional group (amino group) by heating or exposure (wavelength 300 nm or more). This activated functional group can be inactivated by irradiation with deep ultraviolet light (wavelength less than 300 nm). This characteristic makes it possible to fix a gold nanoparticle catalyst at any site on the primer layer to form a gold thin film. In this embodiment, a wiring pattern of a gold thin film was formed by photopatterning utilizing this.
[0086] A primer layer was formed on the TPU substrate in the same manner as in the first embodiment. The primer solution was applied at a spin coat rate of 1000 rpm, and the baking conditions were the same as in the first embodiment. The primer layer surface was then masked with a photomask and exposed to deep ultraviolet light with a wavelength of 254 nm (light source: Deep UV Multilight manufactured by Ushio Inc.) to inactivate some of the functional groups. In this embodiment, the exposure treatment was performed so that the width (wiring width) of the region in which the functional groups were activated on one substrate was 100 μm, 200 μm, and 500 μm. Then, a gold thin film with a thickness of 60 nm was formed in the region activated by the electroless plating process in the same manner as in the first embodiment. Then, a conductivity test during elongation and observation of the surface morphology of the gold thin film during elongation were performed in the same manner as in the first embodiment.
[0087] FIG. 11 shows the results of a conductivity test during stretching in the stretchable wiring board of this embodiment (film thickness: 60 nm, wiring width: 100 μm, 200 μm, 500 μm). FIG. 12 is a microscope photograph of the gold thin film surface during stretching. From FIG. 11, it was confirmed that the gold thin film with a wiring width of 100 μm exhibits conductivity up to an elongation rate of 80%, and the gold thin films with wiring widths of 200 μm and 500 μm are conductive even at an elongation rate of 100%. With regard to the normalized resistance (R / R0), the stretchable wiring boards of each wiring width showed almost the same curve. Looking at the microscope photograph of FIG. 12, the morphology of the cracks during stretching was similar regardless of the wiring width. It is considered that the commonality of the crack morphology is the reason why the normalized resistance is constant regardless of the wiring width. As a result of this embodiment, it was confirmed that in the present invention, a stretchable wiring board in which wiring of about 100 μm was formed by photopatterning can be obtained.
[0088] Sixth embodimentRegarding the manufacturing process of the gold thin film, a stretchable wiring board was manufactured by applying vacuum deposition to compare with electroless plating. First, as preparation of the substrate, a primer liquid was applied to the same TPU substrate as in Example 2 of the first embodiment to form a primer layer. Then, in the same manner as in the first embodiment, a gold nanoparticle catalyst was fixed and a gold thin film with a thickness of 200 nm was formed by electroless plating to produce a sample of the present invention. On the other hand, for comparison, in the vacuum deposition, a gold film (target thickness of 200 nm) was formed by vacuum deposition on the substrate on which the above-mentioned primer layer was formed.
[0089] Thereafter, each of the elastic wiring boards was cut into pieces measuring 1 mm in width and 20 mm in length, similar to the first embodiment. The cut elastic wiring boards were then arranged and fixed on a stage at intervals of 10 mm, and a conductivity test during extension was performed.
[0090] FIG. 13 shows the results of the conductivity test during stretching of the two types of stretchable wiring boards manufactured in this embodiment. The sample in which the gold thin film was formed by vacuum deposition lost conductivity before the elongation rate reached 20%. On the other hand, the sample in which the gold thin film was formed by electroless plating maintained conductivity without disconnection. When the surface of the gold thin film formed by vacuum deposition after the test was observed, wide cracks were found to cross the wiring, so it is believed that the gold thin film formed by vacuum deposition is in a disconnected state. When the surface of the gold thin film formed by electroless plating was observed, no wide cracks were found to cross the wiring. In this embodiment, the wiring material was formed with thin wires with a width of 1 mm, but it is believed that the cracks expanded too much in the gold thin film formed by vacuum deposition. [Industrial Applicability]
[0091] As described above, the stretchable wiring board according to the present invention is composed of a wiring material consisting of a substrate, a primer layer of a predetermined composition, and a gold thin film. The gold thin film, which is the wiring material, exhibits suitable stretchability due to the microcracks contained therein that act when the substrate is stretched. In the present invention, the application of an appropriate primer layer and optimization of the substrate strength improves the elongation rate and improves the conductivity. In addition, in the present invention, the use of gold as the wiring material is advantageous in terms of biocompatibility. The present invention is useful for various devices to which stretchable electronics is applied, and is expected to be used as wearable devices, health care devices, and artificial skin / skin sensors for robots.
Claims
1. A substrate made of an elastic elastomer; a primer layer formed on at least one surface of the substrate, the primer layer including at least a resin component and a crosslinking agent including an amino group; A gold thin film formed on the primer layer, The base material is an elastic wiring board having a Young's modulus of 7 MPa or more and 100 MPa or less.
2. 2. The stretchable wiring board according to claim 1, wherein the gold thin film has a thickness of 60 nm or more.
3. 3. The stretchable wiring board according to claim 1 or 2, wherein the stretchable elastomer constituting the base material is a thermoplastic elastomer of a urethane type, an ester type, an amide type, or an olefin type.
4. 3. The stretchable wiring board according to claim 1 or 2, wherein the resin component of the primer layer contains at least one of an epoxy resin and a polyester resin.
5. Resistance R during elongation when elongated at 50% elongation rate and initial resistance R at 0% elongation rate 0 Ratio of R / R 0 The stretchable wiring board according to claim 1 or 2, wherein the elasticity is 35 or less.
6. A method for producing an elastic wiring board comprising a base material made of an elastic elastomer, a primer layer formed on at least one surface of the base material, and a thin gold film formed on the primer layer, A step of applying a primer liquid containing at least a resin and a crosslinking agent containing an amino group to the substrate to form the primer layer; A step of dispersing a gold nanoparticle catalyst having a particle diameter of 1 nm to 100 nm on a surface of the primer layer; and forming a thin gold film on the surface of the primer layer by electroless plating.
7. In the step of dispersing nano catalyst particles on the surface of the primer layer, the catalyst particles are dispersed at a density of 200 particles / μm 2 More than 1500 pieces / μm 2 The method for producing a stretchable wiring board according to claim 6, wherein the elastic layer is dispersed at a density of: